Loss of custody due to parental alienation - Shinno Pereyra, Vanessa Elizabeth (2021)
The purpose of this paper is to analyze the parental alienation syndrome examined in the judgment handed down by the Second Civil Court of Ica: 00075-2012-01401-JR-FC-01, where the child’s integrity was proven to be damaged. This fact entitled the mother, who did not have custody, to request its change. To this end, suitable evidence was exhibited to obtain custody and for the other parent to lose it.